Peran Administrasi Publik dalam Peningkatan Pelayanan Masyarakat di Kantor Camat Percut Sei Tuan - Simamora, Siti Anisa; Soemitra, Andri (Universitas Muhammadiyah Enrekang, 2024)
The Percut Sei Tuan Subdistrict Office is the administrative center for Percut Sei Tuan District, which is located in Deli Serdang Regency, North Sumatra. As an integral part of the local government structure, the sub-district office plays an important role in managing various aspects of government and public services in the region. With a diverse population and rapid economic growth, the Percut Sei Tuan Subdistrict Office is faced with the challenge of providing efficient and responsive services to the community.Percut Sei Tuan District itself has a rich history, where during the Dutch colonial period this region consisted of two small kingdoms, namely Percut Vocational and Sei Tuan Vocational, which were under the protectorate of the Deli Sultanate. The merger of these two vocations into one sub-district area after the proclamation of Indonesian independence marked the beginning of the modern administrative structure that exists today. This transformation illustrates the long journey from a historic area to a dynamic and developing sub-district.The Percut Sei Tuan Subdistrict Office functions as the center for coordination and implementation of various government programs at the subdistrict level.